PENGUATAN KETAHANAN KELUARGA BERBASIS PEMBERDAYAAN SOSIAL-EKONOMIDI KOTA PEKANBARU MENUJU INDONESIA MAJU 2045 - Murialti, Neng; Widiarsih, Dwi; Darwin, Ranti; Asnawi, Mizan; Hidayat, Muhammad; Hadi, M.Fikry; Marlina, Evi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Family resilience plays a crucial role in achieving social welfare and supporting Indonesia’s Vision 2045, particularly in urban areas such as Pekanbaru, where families face complex economic and demographic challenges. However, low levels of financial literacy and the absence of structured family mapping remain major barriers to strengthening household economic resilience. This community engagement program aims to improve financial literacy, enhance families’ capacity in managing economic resources, and identify internal household potentials through a family mapping approach. The methods employed include educational workshops, community discussions, and practical simulation activities. The results indicate a significant improvement in participants’ understanding of financial recording, household budgeting, and the identification of family assets and economic opportunities. Participants also demonstrated greater motivation to develop home-based enterprises and improve household financial management. The program further strengthened social networks among families, functioning as essential social capital for long-term resilience. These findings confirm that integrating financial literacy and family mapping is an effective strategy for enhancing sustainable family resilience in alignment with Indonesia’s Vision 2045.